The Ystoria Ethyopie in the Cronica Universalis of Galvaneus de la Flamma (d. c.1345) - Bausi, Alessandro; Chiesa, Paolo (Aethiopica, 2019)
The section named Ystoria Ethyopie in the Cronica universalis written by Galvaneus de la Flamma (d. c.1345) depends, according to the writer’s statements, on a Tractatus de mappa whose author is easily identifiable as Giovanni da Carignano (d. c.1330), who drew a famous planisphere of the Mediterranean area. The Tractatus de mappa, as quoted by Galvaneus, reports surprising pieces of news about the Ethiopia of the time and in particular on an event which has been known so far only by a later and generally disregarded source, namely the Supplementum cronicarum of Giacomo Filippo Foresti (first edition 1483): the supposed embassy sent by an imperator Ethiopie to Western Europe at the time of Pope Clement V, that would be the first diplomatic contact between these two areas in the Middle Ages. The Latin text of the Ystoria Ethyopie is edited with an annotated English translation that intends to provide a detailed critical assessment of the document. If no conclusivem evidence in favour of the existence of the embassy emerges and the depiction of Ethiopia in the Ystoria Ethyopie appears to be in several passages influenced by contemporary ideas and expectations, there is no doubt that reliable information on early-fourteenthcentury Ethiopia was directly or indirectly conveyed to Giovanni da Carignano, as we can read it resumed in Galvaneus’s Cronica universalis.